2011
DOI: 10.1123/jpah.8.s1.s103
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Social Contextual Influences on Children’s Leisure-Time Physical Activity: An Ecological Momentary Assessment Study

Abstract: Results describing the value of outdoor and social settings could inform context-specific interventions in this age group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(86 citation statements)
references
References 17 publications
3
80
1
2
Order By: Relevance
“…Previous research is supportive of these findings (Dunton et al, 2011;Perry et al, 2011;Cleland et al, 2008;McCurdy et al, 2010), with some research yielding a positive relationship between and time spent in moderate to vigorous to physical activity in outdoors environments (Jones et al, 2009b;Cooper et al, 2010). However, when examining the association between the variables in this present study, no significant relationship (not presented) was found for moderate to vigorous to physical activity and time spent outdoors.…”
Section: Environmental Differencescontrasting
confidence: 54%
“…Previous research is supportive of these findings (Dunton et al, 2011;Perry et al, 2011;Cleland et al, 2008;McCurdy et al, 2010), with some research yielding a positive relationship between and time spent in moderate to vigorous to physical activity in outdoors environments (Jones et al, 2009b;Cooper et al, 2010). However, when examining the association between the variables in this present study, no significant relationship (not presented) was found for moderate to vigorous to physical activity and time spent outdoors.…”
Section: Environmental Differencescontrasting
confidence: 54%
“…The internal consistency (correlation between items within a scale) was assessed in four studies (Dunton et al 2011Huh et al 2014;Ansell et al 2015). As demonstrated in Table 2, levels ranged from questionable to excellent (George & Mallery, 2003).…”
Section: Reliabilitymentioning
confidence: 99%
“…Dunton et al [32] described physical activity patterns in relation to both location and social context (i.e., number of family and/ or friends nearby). Beets et al [33] found that children were most physically active with other children of their same age in outdoor settings by using a photovoice methodology.…”
Section: Correlates Of Obesitymentioning
confidence: 99%